2021
DOI: 10.3390/curroncol28010045
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Report of Clinical Outcomes in Patients with Melanoma Brain Metastases

Abstract: Background: Brain metastases are observed in more than 40% of all patients with stage 4 melanoma. In recent years, more extensive use of stereotactic radiation (STRT) and the advent of immune checkpoint inhibitors have positively impacted outcomes in patients with metastatic melanoma.brain metastases. Here, we examined real world clinical outcomes of patients presenting with melanoma brain metastases (MBMs). Methods: This retrospective review evaluated MBMs patients treated at The Ottawa Hospital from April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…It is commonly recognized that patients in clinical trials differ from the general patient population due to strict inclusion criteria; however, data from this study suggest that real-world patients with MBM do respond to modern systemic therapies. Other retrospective analyses have shown similar improved outcome for patients with MBM receiving CPI with micPFS of 6.3 months [27] and mOS of 9.0-12.4 months [28,29] compared with the micPFS of 3.0-7.7 months and mOS of 9.7-16.3 months for patients receiving CPI in this study, as shown in Table 2.…”
Section: Discussionsupporting
confidence: 76%
“…It is commonly recognized that patients in clinical trials differ from the general patient population due to strict inclusion criteria; however, data from this study suggest that real-world patients with MBM do respond to modern systemic therapies. Other retrospective analyses have shown similar improved outcome for patients with MBM receiving CPI with micPFS of 6.3 months [27] and mOS of 9.0-12.4 months [28,29] compared with the micPFS of 3.0-7.7 months and mOS of 9.7-16.3 months for patients receiving CPI in this study, as shown in Table 2.…”
Section: Discussionsupporting
confidence: 76%
“…Concurrent or sequential administration of RT and pembrolizumab augmented PFS and OS in a pooled analysis of metastatic NSCLC studies [ 9 ]. Real-world evidence also supports the idea that the use of stereotactic radiation and immunotherapy in melanoma brain metastasis patients may enhance survival [ 10 ].…”
Section: Introductionmentioning
confidence: 82%